The critical speed of a moving load on a prestressed plate resting on a prestressed half-plane - Akbarov, S. D.; Guler, C.; Dincsoy, E. (SPRINGER, 2007)
Within the framework of a piecewise homogeneous body model, with the use of the three-dimensional linearized theory of elastic waves in initially stressed bodies, the dynamical response of a system consisting of a prestressed covering layer and a prestressed half-plane to a moving load applied to the free face of the covering layer is investigated. Two types (complete and incomplete) of contact conditions on the interface are considered. The subsonic state is considered, and numerical results for the critical speed of the moving load are presented. The influence of problem parameters on the critical speed is analyzed. In particular, it is established that the prestressing of the covering layer and half-plane increases the critical speed.
Keywords: critical speed; dynamical response; initial stress; layered half-plane; moving load; INTERFACE STRESS-FIELD; VIBRATION; Mechanics; Materials Science; Polymer Science